The Ideological Component of Judging in the Taxation Context - Nancy Staudt; Lee Epstein; Peter J, Wiedenbeck (Washington University Law Review, 2006)
Despite the vast number of systematic empirical studies of judicial behavior, we know surprisingly little about how and why judges reach decisions in the business and finance context. This void is due, in part, to scholars’ abiding focus on controversies involving civil rights and liberties; indeed, based on the extant literature, it would be easy to conclude that judges, particularly U.S. Supreme Court Justices, spend their days interpreting civil rights–type legislation to the exclusion of all other types of laws. Yet this conclusion is wide of the mark—even a simple count of the Supreme Court’s plenary docket reveals that the Court is more likely to address congressional statutes regulating business and the economy than civil rights legislation. The scholarly focus on civil rights cases, of course, is not itself problematic. The literature on judging in this area is both deep and rich; the studies are numerous and the findings robust. The problem, in our view, is that it is far from clear whether the findings in the civil rights literature can be generalized to all other areas of the law and, in particular, to cases involving statutes regulating business or the economy (“economic controversies”). To be sure, researchers find similarities in the decision making processes across issue areas, but just as often they find differences.
Keywords: Bias (Law) -- Political aspects; Law -- Interpretation & construction; Taxation